Adolescents’ sense of coherence, oral health status, and oral health-related behaviours - Freire MCM, Sheiham A, Hardy R (Blackwell Synergy, 2001)
To investigate the relationship between sense of coherence (SOC) and oral health. It was hypothesised that subjects with better oral health status and better oral health-related behaviours have higher levels of SOC.